ECONOMIC SECURITY DOMINANTS OF THE RUSSIAN INDUSTRIAL ORGANIZATIONS WITH PARTICIPATION OF STATE IN CAPITAL: CHRONICLES OF AVTOVAZ - A. Savin (Вестник университета)
The measures and measures of the Russian state aimed at ensuring economic security of PJSC AvtoVAZ have been examined. The review of the results of nancial and economic activities of the Russian auto concern for the period 2007-2017 is given. Conclusions are drawn about the eectiveness and eectiveness of the actions of the owners of the company aimed at protecting its interests from external and internal threats, an overall assessment of the correctness of the chosen development strategy has been made, and the necessary conditions for its implementation have been claried.